PSYCHOLOGICAL CAPITAL WITH ITS ANTECEDENTS AND CONSEQUENCES: A STUDY ON CIVIL AVIATION EMPLOYEES (Third Sector Social Economic Review, 2019)
This study was conducted to explore the antecedents and the consequences of psychological capital in a structural equation model (SEM). For this purpose, the research was conducted in the light of the data collected through questionnaires with 464 people who are working in the various stages of civilian aviation organizations. When the findings are examined, the organizational justice and core self- evaluations, which are the antecedents of psychological capital, have been shown to influence an individual's psychological capital. In addition, the effects of procedural and distrubutional justice on job satisfaction and organizational commitment, and the effects of distribution and interaction justice on the intention to leave, the medaiting role of psychological capital was found. It is identified that the significant effect of individuals core self perceptions on concequence variables is supported and also the perception of justice has been found to be partially supported. The mediating role of pyschological capital at the effects of individuals’ perception of core self evaluations on job satisfaction and organizational commitment is supported but on the intention to leave is not supported. When all the results are evaluated, found that it is possible to form a model in which the psychological capital is in the center; organizational justice and core self-evaluation are antecedents and job satisfaction, organizational commitment and intention to leave are consequences of the psychological capital.
Keywords: Psychological Capital; Organizational Justice; Core-Self Evaluation; Organizational Commitment; Job Satisfaction; Intention to leave.